2021
DOI: 10.3389/fimmu.2021.667515
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Resetting the Humoral Immune Response by Targeting Plasma Cells With Daratumumab in Anti-Phospholipid Syndrome

Abstract: IntroductionMonoclonal antibodies (mAb) targeting plasma cells are malignant gammopathy designed and approved therapies. In recent years, these antibodies have also been increasingly introduced for non-malignant conditions such as autoimmune-mediated diseases. The Anti-Phospholipid Syndrome (APS) is an immune-mediated disorder in which autoantibodies against phospholipid associated proteins could elicit the activation of the coagulation cascade in specific situations. Therefore, the mainstream treatment for AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…To date, one case report described the use of daratumumab in addition to plasmapheresis and IVIG in a patient with PAPS with recurrent thrombotic events under adequate anticoagulant treatment. After starting daratumumab, the numbers of circulating plasmablasts, and levels of IgG aCL and IgG aβ2GPI declined, starting to reappear after approximately 4 months and no recurrent thrombotic events occurred in the following two years of follow-up [70].…”
Section: Plasma Cell Depletion By Daratumumab In Papsmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, one case report described the use of daratumumab in addition to plasmapheresis and IVIG in a patient with PAPS with recurrent thrombotic events under adequate anticoagulant treatment. After starting daratumumab, the numbers of circulating plasmablasts, and levels of IgG aCL and IgG aβ2GPI declined, starting to reappear after approximately 4 months and no recurrent thrombotic events occurred in the following two years of follow-up [70].…”
Section: Plasma Cell Depletion By Daratumumab In Papsmentioning
confidence: 95%
“…Various "non-criteria" manifestations including thrombocytopenia [61,62,64,65] Thrombosis recurrence [61,63,65] Catastrophic APS [61,65,66] Daratumumab Thrombosis recurrence (case report) [70] Belimumab Diffuse alveolar hemorrhage (case report) [71] Skin ulcers (case report) [71] Catastrophic APS (case report)…”
Section: Rituximabmentioning
confidence: 99%
“…Other agents that might warrant further study include sirolimus, 184 adenosine receptor agonists such as dipyridamole, 154 and plasma cell depleting agents such as daratumumab. 262 Patients are also interested in further study of supplements such as CoQ10, ginger, and vitamin D that have shown promise in preclinical and mechanistic studies. 156 263 264 A review of clinicaltrials.gov in September 2022 identified antiphospholipid syndrome trials recruiting subjects for interventions targeting B cells (belimumab, telitacicept, zanubrutinib), tumor necrosis factor (certolizumab), and innate immunity (hydroxychloroquine).…”
Section: Other Less Common Agentsmentioning
confidence: 99%
“…A notable decline in aCL IgG and aβ2GPI IgG persisted for 108 days after the first dose of medication. Significant clinical improvement was noted after 4 weeks of treatment [96 ▪ ]. Notably, the Daratumumab in Primary Antiphospholipid Syndrome (DARE-APS) trial was recently launched.…”
Section: Daratumumab (Anti-cd38)mentioning
confidence: 99%